2005
DOI: 10.1681/asn.2004100828
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone-Induced Serum and Glucocorticoid-Induced Kinase 1 Expression Is Accompanied by Nedd4-2 Phosphorylation and Increased Na+ Transport in Cortical Collecting Duct Cells

Abstract: Aldosterone plays a central role in Na؉ homeostasis by controlling Na ؉ reabsorption in the aldosterone-sensitive distal nephron involving the epithelial Na ؉ channel (ENaC). Part of the effects of aldosterone is mediated by serum and glucocorticoid-induced kinase 1 (Sgk1), a Ser/Thr kinase whose expression is rapidly induced by aldosterone and that increases in heterologous expression systems ENaC cell surface abundance and activity. Previous work in Xenopus laevis oocytes suggested that Sgk1 phosphorylates s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 42 publications
4
65
0
Order By: Relevance
“…Previous studies on rat (24) and human (36) kidneys indicated that Nedd4-2 is expressed in several nephron portions. To confirm these observations for mouse kidneys, we performed RT-PCR experiments on microdissected tubules from mice (n ϭ 3) that were on the standard-Na ϩ diet (0.8% Na ϩ ).…”
Section: Detection Of Nedd4-2 Mrna In Microdissected Nephron Portionsmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous studies on rat (24) and human (36) kidneys indicated that Nedd4-2 is expressed in several nephron portions. To confirm these observations for mouse kidneys, we performed RT-PCR experiments on microdissected tubules from mice (n ϭ 3) that were on the standard-Na ϩ diet (0.8% Na ϩ ).…”
Section: Detection Of Nedd4-2 Mrna In Microdissected Nephron Portionsmentioning
confidence: 97%
“…Serial cryosections (4 m thick) were incubated with one of the following primary antibodies: Affinity-purified rabbit anti-mouse Nedd4-2 (A26; [24]) diluted 1:500, affinity-purified rabbit anti-mouse Nedd4-2 (A27 [33]) diluted 1:200, rabbit anti-rat ␣-ENaC diluted 1:500 (29), rabbit anti-rat ␤-ENaC diluted 1:500 (29), mouse anti-bovine H-ATPase diluted 1:4 (34), or mouse anti-chicken calbindin D28K diluted 1:20,000 (Swant, Bellinzona, Switzerland). The binding sites of the primary antibodies were revealed by Cy3-conjugated goat anti-rabbit IgG (Jackson ImmunoResearch Laboratories, West Grove, PA) and FITC-conjugated goat anti-mouse Ig (Jackson ImmunoResearch Laboratories) diluted 1:1000 and 1:40, respectively.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…38 Activation of sgk1 through the PI3-kinase pathway may serve to link aldosterone-activated pathways to other modulators of sodium transport such as insulin. 28 Aldosterone increases PI3-kinase activity, perhaps through increased expression of the monomeric G-protein k-ras.…”
Section: Epithelial Aldosterone-induced Proteinsmentioning
confidence: 99%